The Role of Health Promotion in Change Teenage Smoking Behavior - Levi Anatolia S.M. Exposto; Cipriano do R. Pacheco; Januario M. Maia; Oscar Seixas da Cruz; Honoria de F. Cravalho; Santiago J. Pereira; Felisbela A.O. de Oliveira (International Journal Labs, 2022)
The implementation of health promotion programs is important because it is to increase adolescent knowledge about the dangers of smoking, improve adolescent perceptions of smoking, and change adolescent attitudes about smoking to not smoking anymore. The purpose of writing this article is to know and understand the role of health promotion in changing adolescent smoking behavior. The method used in this paper is a systematic review study. 80 articles (2011-2021) were collected in English based on the database of Google, Google Scholar, PubMed, DOAJ, and Emerald Insight. From the 7 articles analyzed, it can be found that the adverse effects of cigarettes on smokers and people around smokers are diseases; some of these diseases are cancer, chronic obstructive pulmonary disease, asthma, acute respiratory infections (ARI), hypertension, stroke, and various other diseases. This impact cannot be felt when initially consuming cigarettes in the early stages. The bad impact will refer to a decrease in individual productivity and performance. One of the strategic efforts to change smoking behavior is through health promotion interventions to change unhealthy lifestyles into healthy ones. Health promotion is one of the efforts to improve public health that focuses on promotion and preventive efforts to provide knowledge in changing adolescent smoking behavior so that they are able to maintain and improve their health status independently.